2018
DOI: 10.1186/s13071-018-3113-0
|View full text |Cite
|
Sign up to set email alerts
|

First report of V1016G and S989P knockdown resistant (kdr) mutations in pyrethroid-resistant Sri Lankan Aedes aegypti mosquitoes

Abstract: BackgroundDengue is a serious arboviral disease in Sri Lanka with a large number of dengue fever (DF) cases every year. Control of the primary vector Aedes aegypti depends upon larval habitat source reduction and insecticide application. However, increases in the number of reported cases suggest the inefficiency of current control strategies and the possibility of resistance to currently used insecticides. Early detection of mutations in the voltage-gated sodium channel (vgsc) gene that confer knockdown resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 21 publications
0
36
1
3
Order By: Relevance
“…aegypti populations in Thailand, in which mosquitoes of the wild type 1016V were homozygous for the F1534C mutation, 1016 heterozygous (1016V and V1016G) mosquitoes were 1534 heterozygous (1534F and F1534C), and mosquitoes with homozygous V1016G mutations were homozygous for the wild type 1534F. In Thailand, the frequency of the F1534C mutation is considerably more common than that of the V1016G mutation [34,36,42], a pattern which has also been reported in Vietnam [43] and Sri Lanka [50]. On the contrary, we found that the V1016G mutation was more common relative to the F1534C mutation.…”
Section: Discussionmentioning
confidence: 58%
“…aegypti populations in Thailand, in which mosquitoes of the wild type 1016V were homozygous for the F1534C mutation, 1016 heterozygous (1016V and V1016G) mosquitoes were 1534 heterozygous (1534F and F1534C), and mosquitoes with homozygous V1016G mutations were homozygous for the wild type 1534F. In Thailand, the frequency of the F1534C mutation is considerably more common than that of the V1016G mutation [34,36,42], a pattern which has also been reported in Vietnam [43] and Sri Lanka [50]. On the contrary, we found that the V1016G mutation was more common relative to the F1534C mutation.…”
Section: Discussionmentioning
confidence: 58%
“…This is consistent with 1534C having more than one origin. Likewise, in Sri Lanka although the triple mutant genotype was found, no individual was homozygote for the three mutations [42].…”
Section: Spatial Analysesmentioning
confidence: 98%
“…F1534C is a phenylalanine to cysteine substitution at position 1534 in domain III, segment 6 [11]. The V1016G kdr mutation is widely distributed across Asian A. aegypti populations [15,16] and has also recently been documented in Aedes albopictus [17,18]. Alone, or in combination with other mutations such as F1534C [13,17,18], these alleles confer significant protection against pyrethroid insecticides [11].…”
Section: Introductionmentioning
confidence: 99%